Effect of Bentonite Prehydration Time on the Stability of Lightweight Oil-Well Cement System - Stephen Adjei; Salaheldin Elkatatny; Abdulaziz Al-Majed (Geofluids)
Lightweight cement systems are used in the weak intervals of petroleum wells. Sodium bentonite is used as an extender in lightweight oil-well cement systems as it prevents excess water and sedimentation of particles, thereby ensuring the formation of homogenous and stable cement sheaths. The extending ability of sodium bentonite is enhanced when prehydrated. However, the optimum bentonite prehydration time and its effect on the stability of lightweight cement systems have not been well established. The objective of this study is to investigate the optimum sodium bentonite prehydration time and correlate it to the stability of lightweight oil-well cement systems. Bentonite suspensions were prepared by vigorous preshearing at 12000 rpm for 5 minutes, followed by aging times of 0, 30, 60, and 120 minutes. The swelling behavior of bentonite was investigated using a laser particle size analyzer. The Herschel-Bulkley model was used to determine the rheological parameters of the experimentally measured shear stress vs. shear rate data of the aged suspensions. The effect of calcium chloride salt on aged bentonite suspensions was investigated. Density measurements and pore space analysis with the nuclear magnetic resonance (NMR) technique were used to investigate the homogeneity of cement-based cores. It was observed that bentonite swells with time and, after 30 minutes, the swelling is insignificant; however, the swelling property did not have any observed impact on the properties of cement systems designed with the bentonite aged at different times. In general, all the lightweight cement slurries exhibited similar properties, in terms of rheology, stability, and homogeneity, regardless of the bentonite prehydration time. These findings indicate that aging bentonite suspension after vigorous preshearing in lightweight cement design is unnecessary and would only contribute to nonproductive time.